A short-term longitudinal study on the development of moral disengagement among schoolchildren: the role of collective moral disengagement, authoritative teaching, and student-teacher relationship quality - Bjärehed, Marlene; Sjögren, Björn; Thornberg, Robert; Gini, Gianluca; Pozzoli, Tiziana (Frontiers in Psychology, 2024)
The aim of this study was to examine whether collective moral disengagement and authoritative teaching at the classroom level, and student-teacher relationship quality at the individual level, predicted individual moral disengagement among pre-adolescent students 1 year later. In this short-term longitudinal study, 1,373 students from 108 classrooms answered a web-based questionnaire on tablets during school, once in fifth grade (T1) and once in sixth grade (T2). The results showed, after controlling for T1 moral disengagement, gender, and immigrant background, that students with better student-teacher relationship quality at T1 were more inclined to score lower on moral disengagement at T2, whereas students in classrooms with higher levels of collective moral disengagement at T1 were more inclined to score higher on moral disengagement at T2. In addition, both collective moral disengagement and authoritative teaching were found to moderate the associations between student-teacher relationship quality at T1 and moral disengagement at T2. These findings underscore the importance of fostering positive relationships between students and teachers, as well as minimizing collective moral disengagement in classrooms. These measures may prevent the potential escalation of moral disengagement in a negative direction.